Prophylactic Effect Of Vitamin E On Carmoisine Food Dye Induced Kidney Damage In Male Mice: Histological, Physiological And Immunological Studies (Applied Biological Research, 2020)
The study evaluates the immunomodulatory effect of vitamin E against the  side effect of synthetic food dye-induced oxidative damage and  nephrotoxicity in male mice. Mice were divided into 4 groups viz., group 1 as  control mice, group 2 received vitamin E (100 mg kg-1 bw), group 3  administered with carmoisine (250 mg kg-1 bw), and group 4 received  carmoisine and vitamin E for 28 days. Nephrotoxicity induce in mice was  assessed by observing the changes in levels of renal markers, and antioxidant  status. Administration of vitamin E significantly restored the levels of renal  functions (urea and creatinine), antioxidants status and immunological  parameters (TNF-a, Cox-2, Bcl-2, CD95 and caspase 3). The prophylactic  role of vitamin E against food dye-induced toxicity may be attributed to their  antioxidant effects and free radical scavenging properties.
Keywords: Antioxidant; carmoisine; mice; nephrotoxicity; vitamin E